Pengaruh Brand Activation Pada Produk Y.O.U Beauty Terhadap Loyalitas Konsumen - Rai Sara Purnama Sari; Velda Ardia (STIKes Ibnu Sina Ajibarang, 2024)
In attracting consumers, every company has various strategies, one of which is to carry out Brand Activation or activities carried out by a brand to change the image or increase sales of a company. One of the beauty brands that does brand activation is YOU Beauty. Related to this, the aim of this research is to find out how much influence brand activation has on YOU Beauty products on followers of the Instagram account @youbeauty.idn, consumer loyalty on followers of the Instagram account @youbeauty.idn, the influence of YOU Beauty brand activation on consumer loyalty. The theory used by Brand Activation is Direct Marketing Activation, Social Media Activation, Promotion Activation, Marketing Event Activation, dan Sponsorship Activation, and Consumer Loyalty includes cognitive, affective, and cognative. The approach in this research is quantitative with an explanatory survey method. The data collection technique was carried out by distributing questionnaires which were given to 81 respondents to followers of the Instagram account @youbeuaty.idn. Sampling using probability sampling technique. Questionnaire collection method used is random sampling. The results of this study indicate that the effect of Brand Activation YOU Beauty as a whole responds well (agree), and the effect of Brand Activation on Consumer Loyalty as a whole responds well (agree) to all variable statements X and Y in the research questionnaire, and the magnitude of Brand influence Activation of YOU Beauty products has an adequate and moderate relationship of 0.575 to Consumer Loyalty of Instagram followers @youbeauty.idn with the percentage of brand activation influencing consumer loyality of 33.1% and while the remaining 66.9% is influenced by other factors.